HORMONAL DISORDERS AND COMPONENTS OF METABOLIC SYNDROME IN PATIENTS AFTER MYOCARDIAL INFARCTION - N. S. Mykhailovska (Zaporožskij Medicinskij Žurnal)
Aims. To explore the features of hormonal disorders and their statistico-correlational interrelations with the components of metabolic syndrome in patients after acute myocardial infarction. Methods and results. The study involved 153 patients with Q-myocardial infarction in age from 40 to 85 years (mean age 62,5±0,90 years) in the acute stage of the disease: 122 - with metabolic syndrome and 31 - without metabolic syndrome. Statistically signifi cant increasing of leptin, insulin, cortisol, C-peptide, TSH levels and decreasing of free T4 level in patients with Q-myocardial infarction with metabolic syndrome were revealed compared with the control group and patients with Q-myocardial infarction without metabolic syndrome. Conclusion. The presence of interrelations between hyperleptinemia and fasting glucose, glycosylated hemoglobin, insulin levels, thyroid-stimulating hormone, index HOMA was determined, which indicates the modulating role of chronic hyperglycemia, hormonal disorders and insulin resistance in the expression and realization of the biological action of leptin in patients with Q-myocardial infarction and metabolic syndrome.